2021
DOI: 10.1111/hdi.12955
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in a patient with COVID‐19 on hemodialysis: Too dangerous to neglect!

Abstract: Neurological manifestations of coronavirus disease 2019 (COVID-19) often have tragic repercussions. Although many reports of neurological complications of severe acute respiratory syndrome coronavirus 2 infection exist, none of them are of patients on hemodialysis, who have a fivefold greater risk of stroke than the general population. In this report, we emphasize the importance of being vigilant for mild stroke in high risk populations-such as patients on hemodialysis-with COVID-19, since these conditions hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Impaired consciousness and dysexecutive syndrome have also been found among COVID-19 patients ( Hampshire et al, 2021 ), especially in concomitancy with other systemic pathologies ( Jacobs et al, 2021 ) and in severe or ICU hospitalized patients ( Rousseau et al, 2021 ). A retrospective study of Wuhan reported disturbances of consciousness in hospital admission in nearly one third of the patients from a sample of 113 deceased patients with COVID-19 ( Chen et al, 2020 ).…”
Section: Neurological Clinical Manifestations Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Impaired consciousness and dysexecutive syndrome have also been found among COVID-19 patients ( Hampshire et al, 2021 ), especially in concomitancy with other systemic pathologies ( Jacobs et al, 2021 ) and in severe or ICU hospitalized patients ( Rousseau et al, 2021 ). A retrospective study of Wuhan reported disturbances of consciousness in hospital admission in nearly one third of the patients from a sample of 113 deceased patients with COVID-19 ( Chen et al, 2020 ).…”
Section: Neurological Clinical Manifestations Of Sars-cov-2 Infectionmentioning
confidence: 99%